Off the grid: utilizing OpenStreetMap for early warning and early action in conflict settings in Sudan - Scholz, Cornelia; Jaime, Catalina; Raju, Emmanuel; Coughlan De Perez, Erin; van Aalst, Maarten (Frontiers in Climate, 2024)
This study investigates the potential of using OpenStreetMap (OSM) data to understand exposure and vulnerabilities to climate-related hazards of Sudan’s most vulnerable populations, such as internally displaced persons (IDPs) or refugees displaced by violent conflict. The rise of conflict in 2023 has triggered a surge in OSM mapping activities, including organized mapping events focused on supporting humanitarian efforts in conflict contexts. These mapping projects aim to address the heightened humanitarian needs driven by the conflict and to assist vulnerable populations impacted by violence. In this study, we conducted key-informant interviews to assess the suitability of using OSM data to enable impact-based forecasting (IbF) as part of Early Warning Early Action (EWEA) to climate-related hazards in data-scarce, conflict-affected regions of Sudan. Our study explores the perspectives of OSM data producers and users, focusing on crucial themes, such as data quality, ethics, user needs, and community inclusion. Our findings reveal that OSM data are perceived to be incomplete in Sudan due to numerous challenges, exacerbated by factors such as the lag in satellite imagery updates compared to the rapidly evolving population movements in conflict-affected areas. Despite various challenges, the overall lack of geospatial data paired with the urgent need to understand the exposure of vulnerable populations to climate-related hazards in the intersection of conflict highlights the usability of OSM as a tool to map high-risk areas to fill these crucial data gaps actively. To do so, addressing the communication gap between OSM producers and users is essential to ensure the effective utilization of collected data for its intended purpose. Moreover, community inclusion emerges as a significant concern, marked by gender disparities and accompanied by challenges in obtaining mapping permissions, as well as the impact of the digital divide. Based on these findings and recent changes in the mapping data landscape due to the escalation of conflict, we advocate for identifying high-risk, unmapped areas vulnerable to climate-related hazards in Sudan and increasing the frequency and spatial coverage of OSM mapping efforts in these regions. Emphasizing community empowerment and ethical data management will be essential to the success of these mapping initiatives.